Improving the crystallization and properties of CZTSSe film by adding NaTFSI in the precursor solution. Issue 16 (17th April 2023) - Xu, Haoyu; Guo, Xuanyang; Yang, Hui; Zhou, Qing; Liu, Shiyan; Gao, Haifeng; Gao, Chao; Yu, Wei
Abstract : NaTFSI addition in the precursor solution of CZTSSe improves the crystalline quality and defect structure of the absorption layer film, thereby enhancing the efficiency of devices. Abstract : In this study, Cu2 ZnSn(S, Se)4 (CZTSSe) films were prepared by a non-vacuum solution method. The efficiency of an as-fabricated CZTSSe solar cell was improved from 8.0% to 10.9% by adding NaTFSI (sodium bis(trifluoromethanesulfonyl)imide) in the precursor solution. It was found that the NaTFSI additive could facilitate the formation and grain-growth of CZTSSe during the selenization of the film. As a result, the size of the crystalline grains in the CZTSSe films increased. Besides, a shallow level acceptor rather than a deep level acceptor could be generated in the CZTSSe films by using the NaTFSI additive. The use of NaTFSI could also decrease the relative content of the low valence Sn 2+, which was believed to be related with deep level defects in CZTSSe. In addition, the effect of the NaTFSI concentration on the properties of CZTSSe solar cells were investigated. We found that excess NaTFSI in the precursor solution would not influence the recombination of the carriers in the neutral region of the solar cell, but could enhance the recombination of the carriers in the depletion region of the solar cell. Therefore, the performances of CZTSSe solar cells were reduced when excess NaTFSI was added in the precursor solution.